STRENGTHENING INDONESIA'S DIPLOMACY IN ECONOMIC RECOVERY AND MITIGATING BUDGET MANAGEMENT IN DEVELOPING COUNTRIES THROUGH THE G20 DIALOGUE FORUM - Hilmi Rahman Ibrahim (Journal of Social Political Sciences, 2022)
The economic recovery agenda of developing countries during the pandemic raises hopes for the G20 as the main international economic forum. Indonesia's chairmanship at the G20 in 2022 is an important moment for the government to strengthen partnerships between developing countries and developed countries in delivering economic recovery and narrowing the gap in inequality in the global economic recovery. Indonesia's role in delivering a productive, resilient and equitable economic recovery reflects the benefits of the G20 forum through the promotion of cooperation and partnerships through Indonesia's chairmanship approach and initiatives in realizing other developing countries more equal to developed countries. Indonesia'sP osisi in various previous international forums has been shown with extraordinary achievements, including through the international forum ASEM (Asia Europe Meeting, Forum Asian Pacific Economi Cooperation (APEC) and G7 which later became Government Twenty G20. Indonesia's reliability in international forums with the ability of global and regional economic diplomacy by utilizing the strategic position carried out in various international meetings including encouraging domestic and foreign climate, is evidence that Indonesia can be a rake on the interests of developing countries , especially those related to financial issues, post-Covid economic recovery and budget mitigation agendas and the impact of economic stability. global over the Russian- Ukranian conflict